Sarab Rog Ka Aukhad Naam: Outlining A Sikh-Specific Cardiac Rehabilitation Program in Peel Region - Uppal, Jasmine (The Meducator, 2022)
“Sarab rog ka aukhad naam” (“The recitation of God’s name cures all diseases”) is a quotation from the Guru Granth Sahib —the Sikh Holy Book— highlighting Sikhism’s perspective on illness, referring to the Guru Granth Sahib as the primary source of guidance regarding issues of health. However, in the decades since this quotation was first written, the burden of chronic illness in the Sikh community has become more severe. Notably, cardiovascular disease (CVD) has become increasingly prevalent within the Sikh and broader South Asian (SA) populations. Several studies have outlined how the SA community has the highest prevalence of CVD in Canada, along with a higher CVD mortality rate compared to other ethnic groups. Although some biological factors may explain the SA community’s increased risk for CVD, there is no denying the social and psychological factors at play. It has been established that sedentary behaviour, depression, and psychological stress increase CVD risk. As such, the fact that SA individuals in Canada are more likely to be sedentary and diagnosed with depression than their non-SA counterparts only intensifies their likelihood of developing CVD. Moreover, much of the SA population in the West exists as visible racial and religious minorities, subjecting them to additional social and psychological harms, including stress stemming from migration and discrimination, all of which contribute to CVD. SA individuals in Canada are also more likely to experience lower quality-of-life one year post-surgical interventions for CVD-related events, as well as increased recurrent CVD events. That is, not only are SAs more likely to develop CVD, but their disease prognosis appears to be worse than non-SAs. As such, improving CVD management procedures for the SA population would prove valuable, given the significant prevalence of the disease in this community. More specifically, areas with a prominent SA population, like the Peel Region of Ontario, should consider providing CVD interventions specific to SAs, such as culturally sensitive rehabilitation programs. As SA is a broad term encompassing many distinct ethnic and cultural backgrounds, this paper recommends focusing on interventions tailored to a specific population within the SA community, to avoid cultural generalizations. For the purposes of this paper, the focus population is the Sikh community, defined specifically as individuals with an ethnic background from the Punjab region in India who practice Sikhism. The Sikh community as a target population is optimal as it falls under the broader SA community and it is one of the largest religious minorities in the Peel Region; thus, this plan would ensure that a sizeable community in the Peel Region receives access to treatment that acknowledges their religious and cultural diversity.10 Peel Regional Health should design a rehabilitation plan specific to the Sikh community for patients diagnosed with CVD, or recovering from a CVD-related incident. However, it is critical to note that there are certain challenges associated with implementing such a program, specifically relating to funding issues and the program’s perceived practicality.